Integrating Buya Hamka’s social criticism into anecdotal text writing instruction - Kurniati Ayu Ningsih; Main Sufanti (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This study aims to analyze the forms of social criticism presented in the novel Buya Hamka by Ahmad Fuadi and to describe how such criticism can be utilized as instructional material for teaching anecdotal text writing at the senior high school level. This research employs a qualitative approach using content analysis. The data consist of words, sentences, and discourses in the novel Buya Hamka that reflect elements of social criticism, as well as information related to the development of anecdotal text teaching materials. The primary data sources are the novel Buya Hamka, published in 2023, and Indonesian language teachers. Data were collected through reading, observation, and note-taking techniques, while data validity was ensured through persistent observation and literature review. Data analysis was conducted using content analysis through heuristic and hermeneutic reading methods. The findings reveal that the novel contains several forms of social criticism: (1) criticism of social injustice reflecting power dominance that does not favor the public; (2) criticism of colonialism as a form of intellectual resistance to oppressive systems; (3) criticism of traditional educational systems, aligned with critical education theory that rejects rote-based learning; and (4) criticism of gender inequality highlighting the importance of equal access to education. These findings indicate that social criticism not only serves as a reflection of social reality but can also be effectively utilized as teaching material for writing anecdotal texts by transforming social issues into short narratives containing humor and satire. Therefore, social criticism in literary works can help students develop critical thinking skills as well as their ability to write anecdotal texts.